Sufficient Schedulability Tests for EDF-Scheduled Real-Time Systems under Interference of a High Priority Task - Santos Jr., J. Augusto; Lima, George (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
We provide four new schedulability tests for a scheduling model according to which there is a high priority task concurrently executed with a set of EDF-scheduled tasks. All tests are proved correct and have their performance evaluated by simulation.